Organic‐Stabilizer‐Free Polyol Synthesis of Silver Nanowires for Electrode Applications. Issue 39 (29th August 2016) - Sim, Hwansu; Bok, Shingyu; Kim, Bongsung; Kim, Minha; Lim, Guh‐Hwan; Cho, Sung Min; Lim, Byungkwon
Abstract: The polyol reduction of a Ag precursor in the presence of an organic stabilizer, such as poly(vinylpyrrolidone), is a widely used method for the production of Ag nanowires (NWs). However, organic capping molecules introduce insulating layers around each NW. Herein we demonstrate that Ag NWs can be produced in high yield without any organic stabilizers simply by introducing trace amounts of NaCl and Fe(NO3 )3 during low‐temperature polyol synthesis. The heterogeneous nucleation and growth of Ag NWs on initially formed AgCl particles, combined with oxidative etching of unwanted Ag nanoparticles, resulted in the selective formation of long NWs with an average length of about 40 μm in the absence of a capping or stabilizing effect provided by surface‐adsorbing molecules. These organic‐stabilizer‐free Ag NWs were directly used for the fabrication of high‐performance transparent or stretchable electrodes without a complicated process for the removal of capping molecules from the NW surface. Abstract : Stable without a stabilizer : Silver nanowires (NWs) were produced by polyol reduction in high yield without an organic stabilizer. Trace amounts of NaCl and Fe(NO3 )3 enabled the heterogeneous nucleation and growth of Ag NWs on initially formed AgCl particles (see picture), and unwanted Ag nanoparticles were removed by oxidative etching. The resulting long NWs could be used directly for the fabrication of transparent or highly stretchable electrodes.